Dental Tourism: Understanding Foreign Patients’ Decisions to Undergo Aligner Treatment in Indonesia - Prastiwi, Ni Luh Gede A. A.; Gorda, Eddy S.; Wirsa, I Nengah; Wisudawati, Ni Nyoman S. (e-GiGi, 2025)
Abstract: Dental tourism is an expanding sector of medical tourism, where patients travel internationally for dental care that is either more affordable or offers higher quality than in their home countries. This study aimed to investigate the push and pull factors that influence foreign patients' decisions to seek dental treatments in Indonesia, particularly Bali, as a prime dental tourism destination. Dental tourism encompasses not only general dental care such as cleaning, fillings, and check-ups but also specialized treatments, including cosmetic dentistry (e.g., veneers, teeth whitening), dental implants, full-mouth rehabilitation, and orthodontic procedures, often involving advanced diagnostic tools and equipment such as digital imaging, CAD/CAM technology, and laser dentistry. Push factors include dissatisfaction with local dental services, high treatment costs, and long wait times in patients' home countries. In contrast, pull factors include Indonesia’s affordable pricing, advanced dental technologies, high-quality care, and the opportunity to combine dental treatment with a vacation experience. The study adopted a systematic literature review (SLR) approach, synthesizing findings from various sources to explore the potential of Indonesia as a leading destination for dental tourism. Interviews with foreign patients revealed high levels of satisfaction, with many appreciating the convenience of receiving both general and specialized dental care while also enjoying their holiday. In conclusion, dental tourism in Indonesia presents a significant opportunity for growth, particularly in destinations like Bali that combine quality dental care with rich cultural experiences. Moreover, the research emphasizes the importance of targeted marketing, regulatory improvements, and investments in advanced technologies to enhance Indonesia’s competitiveness in the global dental tourism market. By addressing these factors, Indonesia can position itself as an attractive and sustainable destination for international dental patients. Keywords: dental tourism; push and pull factors; foreign patients; health tourism